2015
DOI: 10.1155/2015/563727
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Protease Inhibitors in Pregnancy: Maternal and Fetal Considerations

Abstract: Background. Previous studies examining protease inhibitor use in pregnancy and the rate of preterm and small-for-gestational-age infants have yielded conflicting results. Methods. This was a retrospective study of HIV-infected women who delivered singleton infants at our institution between 1984 and 2014. Women with protease inhibitor use were compared to women on regimens without a protease inhibitor as well as those who received no antepartum antiretroviral therapy. Infants were considered preterm if less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“… 83 HIV-positive women should be advised to commence highly active antiretroviral therapy, deliver by cesarean section (CS) and avoid breast-feeding, whereas HCV-positive women should start appropriate therapy so as to eliminate HCV RNA. 84 …”
Section: Prepregnancy Planningmentioning
confidence: 99%
“… 83 HIV-positive women should be advised to commence highly active antiretroviral therapy, deliver by cesarean section (CS) and avoid breast-feeding, whereas HCV-positive women should start appropriate therapy so as to eliminate HCV RNA. 84 …”
Section: Prepregnancy Planningmentioning
confidence: 99%
“…The disorder of these biological processes within the cell can affect the entire system, causing the cells to fail to function. It has also been reported that the disorders of these biological processes leads to growth retardation and pathological pregnancies resulting in fetal mortality (Dodson, Rozance, et al, 2013;Zubor, Kajo, et al, 2014;Duryea, Nicholson, et al, 2015). In our study, the number of offspring in groups of infected males and females was small compared to other groups, which may be due to changes made on placental proteins.…”
Section: Effects Of Chronic Tgondii Infection On Number Ofmentioning
confidence: 45%
“…We were underpowered to detect a significant difference in individual adverse outcomes, but we observed an anticipated percentage of singleton infants affected by PTD, LBW, SGA, and perinatal HIV infection based on previous observational studies of US women with HIV. 3,[8][9][10]13,20,24,25 We made several unexpected observations during this study. Detailed descriptions of ARVs prescribed during pregnancy were recorded for only 30% of the mother-infant pairs in eHARS.…”
Section: Discussionmentioning
confidence: 81%